2009
DOI: 10.1007/s00436-009-1577-8
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 activation by Toxoplasma gondii infection induces the expression of Th2 C-C chemokine ligands and B clade serine protease inhibitors in macrophage

Abstract: Toxoplasma gondii provoked rapid and sustained nuclear translocation of signal transducer and activator of transcription (STAT) 6, a central mediator of interleukin (IL)-4, in macrophage-differentiated human acute monocytic leukemia cells without exogenous IL-4 in western blot and immunofluorescence assay. Phosphorylation of STAT6 occurred immediately after the entry of T. gondii and only by live tachyzoites, not by killed or soluble extract. It was impeded by Janus kinase (JAK) 3 inhibitor and small interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…We further demonstrate that a STAT6/ROP16 interaction can be detected from infected cells and that recombinant, purified ROP16 has intrinsic tyrosine kinase activity in vitro and can directly phosphorylate STAT6 on the crucial activation residue Tyr 641 . Together, these results indicate that ROP16 may directly activate STAT6 upon secretion into host cells; they also provide a molecular basis for observations by Ahn et al (37,38) and Saeij et al (4) that Toxoplasma induces rapid STAT6 activation in an invasiondependent manner. While this manuscript was in preparation, Yamamoto et al (39) described similar results for host STAT3.…”
Section: Discussionsupporting
confidence: 71%
“…We further demonstrate that a STAT6/ROP16 interaction can be detected from infected cells and that recombinant, purified ROP16 has intrinsic tyrosine kinase activity in vitro and can directly phosphorylate STAT6 on the crucial activation residue Tyr 641 . Together, these results indicate that ROP16 may directly activate STAT6 upon secretion into host cells; they also provide a molecular basis for observations by Ahn et al (37,38) and Saeij et al (4) that Toxoplasma induces rapid STAT6 activation in an invasiondependent manner. While this manuscript was in preparation, Yamamoto et al (39) described similar results for host STAT3.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, a proteophosphoglycan produced by L. mexicana within the sand fly vector was shown to induce arginase activity in inflammatory macrophages and enhance intracellular parasite replication [102]. In addition, Toxoplasma gondii was found to activate STAT6 directly [103], and induce arginase through TLR-dependent, but STAT6-independent pathway [104]. Lastly, it was demonstrated that the Ym1, another marker of alternative activation, was induced in macrophages exposed to a helminth antigen [105].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 6% of the target genes in our RNAi data are reported to be regulated by STAT6, by using genome-wide screens performed either on T or B cells of Stat6 À/À mice or STAT6-RNAi experiments, or bound by STAT6 in electrophoretic mobility shift assay (EMSA) (Table S1) (Ahn et al, 2009;Arpa et al, 2009;Bü ttner et al, 2004;Chen et al, 2003;Filen et al, 2009;Gabay et al, 1999;Hebenstreit et al, 2003;Kim et al, 2006;Kurata et al, 1999;Lund et al, 2007;McGaha et al, 2003;Ohmori et al, 1996;Schaefer et al, 2001;Schrö der et al, 2002;Yang et al, 2005;Zhang et al, 2000;Zhu et al, 2002). In addition, few of the genes, such as MAOA, are suggested to be regulated by STAT6 by using indirect methods such as in silico predictions (Chaitidis et al, 2004).…”
Section: Immediate Target Genes Of Stat6mentioning
confidence: 96%